Geography and cultural diversity. territorialization of a gypsy group in goiás, brazil (2009)
The redefinitions of humanist and cultural geography have allowed a greater approach to identity construction and its relation with territorialization processes. However, there are few works regarding processes of cultural exclusion, specifically refering to the gypsy people. This paper’s main purpose is to emphasize the pertinence of geography in the study of cultural diversity, by presenting the territorialization process of the romaní people (or gypsy people) in Ipameri, a city located in southwestern Goiás, state of Brazil. The methodology used arises from cultural geography, in which fieldwork, oral history and interviews allow a better understanding of the territorial perspective of the romaní, bound to cartographic perceptions and representations. This text intends to identify the existence of territories that have been excluded —as in the case of the romaní— and to understand the process of territorial construction and cultural identity.